PENGALAMAN MASYARAKAT SUKU BATAK TOBA PASCA TERPAPAR COVID-19 DI DESA PANIARAN SIBORONGBORONG - Rosha Hutasoit; Lenny Lusia Simatupang (STIKes Murni Teguh, 2023)
Coronavirus disease 2019 (Covid-19) is a disease where the rate of spread is relatively fast. This disease is caused by a virus that attacks the human respiratory system. Prevention of infectious diseases can minimize contact between infected individuals and other susceptible individuals. This study aims to explore and find out how the experiences of the Batak Toba people after being exposed to COVID-19. This research method is a qualitative method with a phenomenological method in Paniaran Siborong-borong Village. The samples used with purpose sampling technique were 10 people. Data analysis techniques used in qualitative research include interview transcripts, data reduction, analysis, data interpretation and triangulation. The results of this study obtained four themes regarding the experience of the Toba Batak community after being exposed to Covid-19 in Paniaran Siborongborong Village. The conclusion in this study, there are four themes, as follows (1) The Process of Being Affected by Covid-19 Infection in the Community, (2) Symptoms experienced after being infected with Covid-19, (3) Efforts made by participants in prevention and treatment, (4) Feelings condition When infected with Covid-19. Abstrak Coronavirus disease 2019 (Covid-19) merupakan penyakit dimana tingkat penyebarannya tergolong cepat. Penyakit ini disebabkan adanya virus yang menyerang sistem pernafasan manusia. Pencegahan penyakit menular dapat meminimalisir kontak antar individu yang terinfeksi dengan individu lainnya yang rentan ditular. Penelitian ini memiliki tujuan untuk menggali dan mengetahui bagaimana pengalaman masyarakat suku batak toba pasca terpapar covid-19. Metode Penelitian adalah kualitatif dengan desain fenomenologi di Desa Paniaran Siborong-borong dan teknik pengumpulan sampel adalah purpose sampling sebanyak 10 orang. Analisa data yang digunakan dalam penelitian kualitatif mencakup transkip hasil wawancara, reduksi data, analisis, interpretasi data dan triangulasi. Hasil mendapatkan empat tema tentang Pengalaman Masyarakat Batak Toba Pasca Terpapar Covid-19 Di Desa Paniaran Siborongborong. Kesimpulan dalam penelitian ini terdapat empat tema yaitu: (1) Proses Terkena Infeksi Covid-19 Pada Masyarakat, (2) Gejala Yang dialami setelah terinfeksi Covid-19, (3) Upaya yang dilakukan partisipan pada Pencegahan dan pengobatan, (4) Kondisi Perasaan Pada saat terinfeksi Covid-19.